Effects of household cooking methods on changes of tissue structure, phenolic antioxidant capacity and active component bioaccessibility of quinoa. (15th July 2021) - Gu, Ruijuan; Chang, Xiaowen; Bai, Guotao; Li, Xiang; Di, Yan; Liu, Xuebo; Sun, Lijun; Wang, Yutang
Graphical abstract: Highlights: Structures, components and its bioaccessibility were changed after cooking. Germination reduced tocopherol content and improved bioaccessibility of ferulic acid. Steaming decreased phenolic content and improved bioaccessibility of tocopherol. Baking had minimum effect on the structure and components of four colors of quinoa. Abstract: The effects of four household cooking methods including germination (Ger), baking, normal pressure steaming (NPS) and high pressure steaming (HPS) treatments, on tissue structure, tocopherol, antioxidant capacity and active component (ferulic acid and tocopherol) bioaccessibility of different colored quinoa were investigated. The results showed that Ger increased the phenolic contents and antioxidant capacity, but decreased the contents of tocopherol. The steaming processes destroyed the tissue structure of quinoa to a large extent, causing a significant loss of phenolic/flavonoid components and the resultant decreased antioxidant capacity. The baking process had minimum impact on tissue structure and active components due to the protection of hypocotyl-radicle axis. Besides, through in vitro simulated digestion, Ger improved the bioaccessibility of ferulic acid, and steaming processes increased that of tocopherol. Conclusively, to develop the expected nutritional value of quinoa, several alternative cooking methods are provided according to the respective effects.